THE EFFECT OF CHARISMATIC LEADERSHIP, ORGANIZATIONAL COMMUNICATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (CASE STUDY AT THE AL-QUR’AN WAQF BOARD, HEAD OFFICE JAKARTA) - Liana Fitria; Herminingsih Anik (Dinasti Publisher, 2021)
Research entitled